Evaluating the roles of microRNAs associated with nonalcoholic fatty liver disease in hepatocellular carcinoma tumorigenesis: a systematic review and network analysis - Peng, Qinghua; Zhu, Xiaoning; Jiang, Yuanyuan; Peng, Mengyun; Zheng, Ding; Wang, Xiaodong; Cheah, Yoke Kqueen; Wang, Jing (Frontiers in Medicine, 2024)
Nonalcoholic fatty liver disease (NAFLD) has become the leading cause of chronic liver disease worldwide. Hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide, with high morbidity and mortality. The rapidly increasing incidence of NAFLD is becoming an essential precursor of HCC globally. MicroRNAs (miRNAs) are involved in the progression of NAFLD and HCC. This study aims to evaluate the roles of miRNAs associated with NAFLD in HCC tumorigenesis through systematic review and data mining analysis. The roles of the potential miRNA and its target genes in NAFLD and HCC were evaluated by bioinformatic analysis. First, MIR122 was identified as the potential miRNA associated with NAFLD and HCC.Then, MIR122 expression was significantly lower in HCC patients, and higher MIR122 levels were associated with significantly better overall survival. Next, the biological functions of MIR122 and target genes were predicted to be involved in inflammation, fibrosis, cell proliferation, invasion, metastasis, and apoptosis. In particular, the FOXO signaling pathway may regulate the above biological functions. In the end, MIR122 was suggested to be involved in progressing from NAFLD to HCC through the PI3K/AKT/FOXO pathway.